Single-Cell Transcriptome Analysis Reveals Intratumoral Heterogeneity in ccRCC, which Results in Different Clinical Outcomes - Hu, Junyi; Chen, Zhaohui; Bao, Lin; Zhou, Lijie; Hou, Yaxin; Liu, Lilong; Xiong, Ming; Zhang, Yuhan; Wang, Bin; Tao, Zhen; Chen, Ke (Molecular therapy, 2020)
Clear-cell renal cell carcinoma (ccRCC) is the most common histological type of RCC. To investigate the intratumoral heterogeneity of ccRCC, we analyzed single-cell RNA-sequencing data and identified 15 major cell types, along with 39 subgroups of cells derived from tumor or non-malignant tissues, and confirmed their presence by immunofluorescence staining in tissue chips. In this study, we verified that T cell exhaustion was the key factor responsible for the immunosuppressive property of ccRCC tissues, which was significantly related to poor prognosis. We also found that abnormal metabolic patterns occurred not only in cancer cells, but also in tumor-infiltrating stromal cells. Based on the fraction of each cell cluster detected by CIBERSORTx, 533 patients from The Cancer Genome Atlas (TCGA) KIRC dataset were divided into three groups. One group, which showed a lesser proportion of activated CD8+ cells and greater proportion of exhausted CD8+ cells, was associated with a poor prognosis. Hence, the blockade of immunosuppressive checkpoints, not only PD-1, but also LAG3, TIM-3, and other inhibitory checkpoints, could serve as a potential target for ccRCC immunotherapy. Our work will further the understanding of the heterogeneity among ccRCC tissues and provide novel strategies for treating ccRCC. [Display omitted] Via single-cell transcriptome analysis, we investigated the intra-tumoral heterogeneity of clear-cell renal cell carcinoma (ccRCC) and identified the composition inside tumor tissues. With a computational pipeline, we revealed the clinical significance of tumor-infiltrating cells and provided novel strategies for treating ccRCC.